Two-step-7-Pink Rule: A Practical Tool for the Dermoscopic Evaluation of Fully Amelanotic Skin Lesions - Riccardo Pampena; Stefano Migliorati; Giovanni Paolino; Michela Lai; Nicola Lippolis; Stefania Guida; Stefania Borsari; Sebastiano Pellerone; Sofia Maria Di Ciaccio; Elvira Moscarella; Giovanni Pellacani; Giuseppe Argenziano; et al. (Dermatology Practical & Conceptual)
Introduction: The diagnosis of fully amelanotic skin tumors is difficult on clinical and dermoscopic examination.